Optimizing Social Media Marketing Strategies to Improve The Business Sustainability of MSMEs - Lies Hendrawan Krisnawati; Indra Siswanti; Yanto Ramli; Cristina Catur Widayati (Amkop Management Accounting Review (AMAR), 2026)
Social media marketing strategies are a key element in maintaining and improving the sustainability of Micro, Small, and Medium Enterprises (MSMEs) businesses. The research, in the form of a Systematic Literature Review (SLR) PRISMA, used a Boolean search using PICO and SPIDER and identified 2446 initial articles from international journals (Scopus, ScienceDirect, Springer, Wiley, IEEE, Web of Science, and Google Scholar). The data was omitted, so that the final results were 32 journals. Bibliomatrix analysis, in the form of Vos Viewer, along with Inclusion, Exclusion, and Quality Criteria. Research shows that social media marketing strategies significantly improve MSME sustainability through customer engagement, relevant content, and the integration of adaptive digital technologies. The theoretical benefits of formulating social media relationships, which are helpful in the academic world, and the practical benefits of this approach as a digital strategy for MSME actors, as well as its implications for government and policy, for transformation recommendations.